2019
DOI: 10.2134/cftm2018.12.0100
|View full text |Cite
|
Sign up to set email alerts
|

Irrigation Water Management Technologies for Furrow-Irrigated Corn that Decrease Water Use and Improve Yield and On-Farm Profitability

Abstract: Irrigation water management practices decreased total water applied by 39.5%.• Irrigation water management practices increased corn grain yield by 6.5 bu/acre.• Irrigation water management practices increased irrigation water use efficiency by 51.3%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(53 citation statements)
references
References 30 publications
5
48
0
Order By: Relevance
“…There is compelling evidence that even minor modifications to existing irrigation and agronomic practices in the Mid-South USA region can result in noticeable water savings while achieving similar yields at harvest [7][8][9][10]. As anticipated, the practices evaluated in those studies and considered here are not universally adopted in the area.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…There is compelling evidence that even minor modifications to existing irrigation and agronomic practices in the Mid-South USA region can result in noticeable water savings while achieving similar yields at harvest [7][8][9][10]. As anticipated, the practices evaluated in those studies and considered here are not universally adopted in the area.…”
Section: Introductionmentioning
confidence: 80%
“…The use of Soil Moisture Sensors (SMS) for scheduling has the potential to save as much as 50 percent of total water applied [30]. Agronomic studies in the area showed that SMS could help improve water use efficiency in furrow irrigated soybeans [7] and corn [10] by reducing water use without reductions in yields when compared to conventional farmer-managed scheduling.…”
Section: Irrigation and Water Conservation Practicesmentioning
confidence: 99%
“…Similar to the results from this study, sensor-based irrigation scheduling either maintained or improved IWUE for the majority of row crops seeded in the midsouthern United States. Scheduling with sensors rather than the producer standard increased IWUE on production-scale irrigation sets 36, 51, and 70% for soybean, corn, and rice, respectively (Bryant et al, 2017;Gholson, 2020;Spencer T A B L E 5 Soybean grain yield, water use, irrigation water use efficiency (IWUE), and returns above irrigation costs for season-long threshold treatments in a furrow-irrigated soybean study comparing season-long and growth stage-based irrigation threshold treatments near Stoneville, MS, from 2015 through 2017 ., 2019). Transitioning from the producer standard to a −90 cbar threshold either had no effect or increased IWUE of cotton up to 260% (Plumblee et al, 2019).…”
Section: Season-long Threshold Analysismentioning
confidence: 99%
“…Irrigation water use efficiency improvement and crop productivity are major concerns in the agricultural sector [1]. Water use efficiency is directly associated with farm profitability, soil health, water quality, water conservation, and sustainable use [2,3]. According to the United States Department of Agriculture (USDA) report, around 70% of the total cropland was irrigated using groundwater and surface water sources in 2017 in Louisiana (United States Department of Agriculture (USDA), Crop Acreage Data (2017).…”
Section: Introductionmentioning
confidence: 99%